Handbook of Scales in Tourism and Hospitality Research - Gursoy, D; Uysal, M.; Sirakaya-Turk, E.; Ekinci, Y.; Baloglu, S. (CABI, 2015)
By introducing the importance of measurement and scales and providing groupings of existing scales The Handbook of Scales in Tourism and Hospitality Research serves as the state of the art reference book in the field of tourism, hospitality ...